Uso de canabinoides no tratamento da doença de Alzheimer: uma revisão integrativa - CARNEIRO, Natan Silva (2024)
Alzheimer's disease is a neurodegenerative pathology, which courses mainly with gradual memory loss and cognitive-behavioral symptoms, being the most common type of monitored. With the advancement of science, several drugs were discovered and used in an attempt to control symptoms. However, some patients do not respond well to these medications or have behaviors and symptoms that deviate from conventional treatment, requiring more effective and less aggressive substances. In this context, the use of cannabidinoids is effective, presenting clinical and social gains for patients. Thus, this study is an integrative review, which seeks to access the main scientific works by grouping information in order to prove the benefits of using these in the treatment of AD. We can conclude that the uso of these brought improvements in agitation, aggressiveness, food refusal and pain, in addition to important gains in short and long-term memory, cognitive function, behavior and quality of life.